Potential Benefits of Forest Litter Biomass in Agriculture - Ray, Lala I.P.; Behera, L.K.; Dash, Benukantha; Singh, Bikaram (Indian Forester, 2024)
The global forest cover is roughly 4,059 million hectares (mha) and the quantum of forest litter fall from different forest types is estimated to be around 3-12.41 ha-1 per annum. Forest litters play a significant role in nutrient cycling, ecosystem turnover rates and the global carbon cycle. The forest litter biomass can suitably be incorporated into agricultural fields for increasing soli organic carbon, soil moisture conservation and soil fertility enhancement It has also been observed that a significant portion of the forest litter mass is burnt in situ due to forest fire and anthropogenic activities causing multifarious health as well as environmental hazards. The forest litter mass is a potential source of bio-mulch for sustainable soil health and productivity management in the agriculture fields. Organic mulching enhances crop yield under limited or water-deficit soils and helps in maintaining salubrious soil temperature, soil structure, and reduces soil erosion in the long run. Application of forest litter mass in agricultural soils improves the soli health and productivity on one hand and reduce the forest fire hazard on the other. This article summarizes various aspects of the use of forest litter mass as bio-mulch in the agricultural sector and other ancillary benefits.